2023
DOI: 10.1136/gutjnl-2023-330691
|View full text |Cite
|
Sign up to set email alerts
|

Changing prevalence of chronic hepatitis B virus infection in China between 1973 and 2021: a systematic literature review and meta-analysis of 3740 studies and 231 million people

Zhenqiu Liu,
Chunqing Lin,
Xianhua Mao
et al.

Abstract: ObjectiveChina concentrates a large part of the global burden of HBV infection, playing a pivotal role in achieving the WHO 2030 global hepatitis elimination target.MethodsWe searched for studies reporting HBV surface antigen (HBsAg) seroprevalence in five databases until January 2023. Eligible data were pooled using a generalised linear mixed model with random effects to obtain summary HBsAg seroprevalence. Linear regression was used to estimate annual percentage change (APC) and HBsAg prevalence in 2021.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…The prevalence and magnitude of reduction in chronic HBV infection vary by geographical region and across other strata of the Chinese population. In the mainland of China, the highest prevalence in the latest study period was observed in the Xizang Autonomous Administrative Region (formerly known as Tibet), followed by other provinces mostly clustered in southern China (Hainan, Jiangxi, Fujian, Guangxi, Guangdong and Qinghai), whereas the lowest seroprevalence was observed in Beijing and Shanxi [ 53 ]. This geographical heterogeneity in HBsAg prevalence is consistent with that observed in a recently published study among nearly 100 million pregnant women across 31 provinces in China [ 54 ].…”
Section: Challenges In Reducing the Heavy Disease Burden Of Chbmentioning
confidence: 99%
“…The prevalence and magnitude of reduction in chronic HBV infection vary by geographical region and across other strata of the Chinese population. In the mainland of China, the highest prevalence in the latest study period was observed in the Xizang Autonomous Administrative Region (formerly known as Tibet), followed by other provinces mostly clustered in southern China (Hainan, Jiangxi, Fujian, Guangxi, Guangdong and Qinghai), whereas the lowest seroprevalence was observed in Beijing and Shanxi [ 53 ]. This geographical heterogeneity in HBsAg prevalence is consistent with that observed in a recently published study among nearly 100 million pregnant women across 31 provinces in China [ 54 ].…”
Section: Challenges In Reducing the Heavy Disease Burden Of Chbmentioning
confidence: 99%
“… 4 China has the highest HBV infection burden in Asia, and although the prevalence of HBV in China has decreased in the past 40 years, the prevalence of hepatitis B surface antigen (HBsAg) in some subpopulations is still high in China. 5 Furthermore, intravenous drug users are at relatively high risk of contracting hepatitis C, and those who have been previously infected with this disease but have not been cured account for the majority of existing patients. 6 China is a high epidemic area for viral hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…The research report by Polaris Observatory Collaborators indicates that the global HBV prevalence in 2022 is estimated to be 3.2%, corresponding to 257.5 million HBsAg-positive individuals [ 2 ]. In China, the prevalence of HBsAg among the general population in 2021 was 3%, and the estimated chronic HBV infection was 43.3 million [ 3 ]. China accounts for a significant portion of the global burden of HBV infections and plays a key role in achieving the World Health Organization’s 2030 global hepatitis elimination target [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In China, the prevalence of HBsAg among the general population in 2021 was 3%, and the estimated chronic HBV infection was 43.3 million [ 3 ]. China accounts for a significant portion of the global burden of HBV infections and plays a key role in achieving the World Health Organization’s 2030 global hepatitis elimination target [ 3 ]. The persistent presence of covalently closed circular DNA (cccDNA) in hepatocytes is a key obstacle for a cure of chronic hepatitis B (CHB) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%